Prestasi Belajar ditinjau dari Kedisiplinan pada Siswa Perguruan Setia Budi Abadi Perbaungan - Jeslin Jeslin; Sarinah Sarinah; Achmad Irvan Dwi Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship between discipline and academic achievement. The hypothesis of this study states that there is a positive relationship between discipline and academic achievement. Subjects of this study were 123 students of Perguruan Setia Budi Abadi Perbaungan. Data were obtained from the school report card to measure academic achievement and data were obtained from a scale to measure discipline. Data were analyze by Spearman’s Rank Order Correlation with SPSS 20 for Windows. The results of data analysis showed that the correlation coefficien was 0,688 (p<0,05). It showed that there is a positive relationship between discipline and academic achievement. From these results it is concluded that the hypothesis stating there is a positive relationship between discipline and academic achievement is acceptable.